The development of Hypromellose based semisolid 3D printing inks for drug delivery (Transactions on Additive Manufacturing Meets Medicine, 2021)
3D printing is a promising method for producing medicines to tailored individual patient’s needs in the optimal dose and drug combinations which subsequently leads to enhanced therapeutic outcome. Here, we developed semisolid ink formulations based on hydroxypropyl methylcellulose (HPMC). We investigated the effects of additives including PVP and SiO2 and a model drug, paracetamol, on the HPMC ink rheology behaviour and shape fidelity when produced using semisolid 3D extrusion printing. The formulations were extruded from the printing nozzle and laminated layer-by-layer. The current study presents novel drug-loaded HPMC-based inks for 3D construct fabrication for potential drug delivery applications.
Keywords: Semisolid 3D printing; Drug delivery; Rheological behaviour